Pemahaman Hadis dan Implikasinya pada Praktek Keagamaan Jamaah Tabligh (Kajian Living Hadis di Kota Bengkulu) - Aan Supian; Ahmad Farhan (AL QUDS : Jurnal Studi Alquran dan Hadis, 2021)
Understanding Hadith and Its Implications on the Religious Practices of the Tablighi Jamaat (Study of Living Hadith in Bengkulu City)This study was conducted to find out how the Tablighi Jamaat's understanding of the Sunnah of the Prophet and to describe the practice of the Prophet's traditions among the Tablighi Jamaat. The type of this research is a field research that used a phenomenological approach with a qualitative descriptive method. Research informants are members of the Tablighi Jamaat who were randomly selected based on their needs. In order to obtain the data in this study, the researcher used direct observation methods, extracting the information through interview and documentation based. The research findings confirmed that the Tablighi Jamaat defined the term of sunnah tends to lead to the definition that narrated by Hadith scholars. The definition of hadith in question is all things that are relied on the Prophet Muhammad either when he has been appointed as a prophet or afterward (Qabla al-Bi’stah ay Ba’dahu), including every word and deed, nature and things. Therefore, there is an understanding that the Tablighi Jamaat becomes necessary to follow everything that came from the Prophet Muhammad. Those all were stated as sunnah, even though the practice of the Prophet Muhammad was in the capacity of an ordinary human being. In general, the Tablighi Jamaat used the works of Maulana Muhammad Zakaria Yusuf al-Kandahlawi and Maaulana Muhammad Yusuf al-Kandahlawi as references in worships and charity. Moreover, the Muntakhab Ahadis and Fadhail A’mal books are the main consumption in every taklim and recitation activities (read; bayan) of the congregation. However, not all congregations knew and even memorized the hadiths that used as evidence in doing charity